EVALUASI SISTEM AKUNTANSI PEMBELIAN PADA PT. JENGGOLO MAJU MAPAN DI KEDIRI - Agnesia, Briggita; Winarko, Sigit Puji; Zaman, Badrus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Jenggolo Maju Mapan is a manufacturing company, especially in bread commodities. The purpose of this final project is to find out and evaluate how the implementation of the purchasing accounting system at PT. Jenggolo Forward Established. In preparing this final project, the writer uses qualitative methods, with descriptive research techniques where more descriptions are made from the results of interviews, observations, and documentation. The data used are primary and secondary data. Based on the results of the final project which was examined by the author, PT. Jenggolo Maju Mapan has implemented procedures in the accounting system, the company has divided functions for internal control, division of functions such as warehouse functions, purchasing functions, receiving functions, and accounting functions. Accounting procedures can run well because of the supervision of the directors and managers so that healthy accounting practices grow. However, there were found obstacles that were found to hinder the effectiveness of purchasing performance. The purchasing department exceeded the payment limit because there was a slip of travel document, and the travel document was carried away by the supplier thereby hampering the payment process.